Microbial proportion and heterotroph CO2 flux from drainage peatland under oil palm plantation - Eka Lupitasari; Rahayu Widyastuti; Heru Bagus Pulunggono (Brawijaya University, 2021)
The difference in soil layer can affect heterotroph respiration that means CO2 fluxes from microbial decomposition in peatlands. Oil palm plants release root exudates transported to other places, i.e., shrub, by water movement, which can stimulate microbial activity. This study was conducted to learn the effects of differences of the soil layer and distance from the trunk in drainage peatland under oil palm plantation on total bacteria, fungi, cellulolytic bacteria, ligninolytic fungi, and heterotroph fluxes CO2, then compared to a shrub. Heterotroph respiration decreased with soil layer depth, where at the layer 0-20 cm released amount of CO2 as much 6.07 + 1.76, at 20-40 cm was 5.18 + 0.50, and at 40-60 cm 5.27 + 1.20 mg CO2 100 g-1 day-1, and tended higher than in shrub where a layer of 0-20 cm released 5.51 + 1.69, then decrease at 20-40 cm to 4.83 + 1.38, and at 40-60 cm 4.30 + 1.08 mg CO2 100 g-1 day-1. Total bacteria (107 CFU g-1) and fungi (105 CFU g-1) were higher than total cellulolytic bacteria (103 CFU g-1) and ligninolytic fungi (102 CFU g-1) in both under oil palm plantation and shrub. Organic acids affected the abundance of total bacteria and fungi but did not affect cellulolytic bacteria and ligninolytic fungi on both sites, as shown by a lower population and low cellulose and laccase enzymes. These findings showed that heterotroph CO2 flux tended higher in oil palm plantations and lignocellulolytic microbes are not the only source of heterotroph respiration.